Impact of the Covid-19 Pandemic on Catfish Farming Income in Kampar Regency - Syafira Aulia Rangganis; Anna Fariyanti; Dwi Rachmina (Jurnal Perikanan Universitas Gadjah Mada, 2023)
The Covid-19 pandemic that has occurred since 2020 is thought to have a different magnitude of impact on each type of catfish farming in Kampar Regency. This study aimed to analyze the structure of costs and revenues as well as differences in income from catfish farming based on the type of farming in Kampar Regency before and during the Covid-19 pandemic. This research was carried out in Koto Mesjid Village and Kuok Village from November 2021 to June 2022. The sample in this study was 60 farmers who farmed catfish for smoked fish raw materials were determined using a purposive sampling technique, and 60 farmers who farmed catfish for consumption were determined using a simple random sampling technique. The analytical method used is the structure of costs and revenues analysis, income analysis, and different tests. The results of the analysis show that there is a significant difference between income earned before and during the Covid-19 pandemic. However, there is no significant difference in income obtained between types of farming. Based on the R/C ratio of cash costs, catfish farming as raw material for smoked fish is financially feasible. However, based on the R/C ratio of total costs, no catfish farming is economically feasible to run during the Covid-19 pandemic.